Automatic Synthesis Method for Multi-speed Automatic Transmission Configuration - Ke, Tao; Ding, Huafeng; Kecskemethy, Andrés (Mechanism and machine theory, 2025)
•A unified matrix model of automatic transmission (AT) mechanism is introduced.•A matrix model-based AT mechanism configuration synthesis method is proposed.•The method is suitable for synthesizing complex AT configurations with any gear requirements. Automatic transmissions (AT) configuration with more pleasant driving and convenient operation have seen increasing attention in the fast-growing automobile industry. This paper presents a new matrix model describing the planetary gear train (PGT) structure, shifting elements layout and clutching sequence of AT configuration. An automatic configuration synthesis method of multi-speed AT is proposed based on this model. Firstly, feasible PGT structures are synthesized by generating corresponding structural matrices subject to structural constraints. Secondly, the shifting elements layouts of each structural matrices are synthesized through distributing brakes and clutches. Thirdly, automatic kinematic analysis of all possible gears is performed to acquire the feasible clutching sequence matrices. Finally, taking the thirteen-speed AT configuration synthesis as an example, the proposed automatic configuration synthesis method was applied to obtain five feasible configurations. Furthermore, the proposed method can automatically synthesize the configuration of other multi-speed AT with multiple planetary gear sets (PGSs) and multiple shifting elements by setting new design constraints.